CULTURAL AWARENESS THROUGH PROVERBS: DEVELOPING INTERCULTURAL COMPETENCE IN ENGLISH LANGUAGE LEARNERS - Rejeki, Sri (Universitas Muria Kudus, 2024)
AbstractProverbs serve as powerful linguistic and cultural tools, encapsulating collective wisdom, values, and beliefs. This study investigates their potential impact on English language learners' cultural awareness and cross-cultural understanding. By analyzing proverbs, students gain insights into cultural differences and similarities. Proverbs serve as gateways to cultural understanding, bridging language learning and intercultural competence. The study employs qualitative methods. Specifically, it explores the following questions: (1) Can Proverbs Enhance Cultural Awareness? (2) Indonesian Proverbs and Cultural Values. This research highlights the importance of thoughtful integration of proverbs in language teaching to foster cultural awareness among English language learners.